1996
DOI: 10.1007/bf02337889
|View full text |Cite
|
Sign up to set email alerts
|

Substrate mobilization and hormonal changes in rainbow trout (Oncorhynchus mykiss, L.) and common carp (Cyprinus carpio, L.) during deep hypoxia and subsequent recovery

Abstract: Substrate mobilization and hormonal changes in rainbow trout(Oncorhynchus mykiss, L.) and common carp (Cyprinu$ carpio, L.) during deep hypoxia and subsequent recovery Accepted: 7 May 1996 Abstract Common carp (at 20 °C) and rainbow trout (at 15 °C) were fitted with an indwelling cannula in the dorsal aorta. The fish were exposed to a controlled decline of water pO2 followed by 90 min deep hypoxia at 0.3 kPa (carp) or 4.8 kPa (trout). Thereafter, normoxic recovery was monitored in both species for 48 h. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 42 publications
6
60
3
1
Order By: Relevance
“…Although there are no previously published data for chub with which to compare these results, the levels of plasma glucose and plasma lactate observed in unstressed chub and the changes in these metabolites which were observed in stressed chub during the present study are similar to those reported for related species, the carp (Hertz et al, 1989;Dabrowska et al, 1991;van Raaij et al, 1996) and roach . There was again evidence of a sexually dimorphic response to a stressor in that glucose levels were significantly related to sex, being higher overall in female than male chub.…”
Section: Discussionsupporting
confidence: 86%
“…Although there are no previously published data for chub with which to compare these results, the levels of plasma glucose and plasma lactate observed in unstressed chub and the changes in these metabolites which were observed in stressed chub during the present study are similar to those reported for related species, the carp (Hertz et al, 1989;Dabrowska et al, 1991;van Raaij et al, 1996) and roach . There was again evidence of a sexually dimorphic response to a stressor in that glucose levels were significantly related to sex, being higher overall in female than male chub.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the control plasma concentrations of catecholamines and cortisol, the 2 main parameters to determine stress in fish (Donaldson 1981), were close to the lowest values reported in fish (Van Raaij et al 1996). So, it could be supposed that the impact of cannulation was not significant.…”
Section: Discussionmentioning
confidence: 51%
“…Means ± SE (n = 18 at t = 0 and 6 h at the other sample times). *Values significantly different from control data at p < 0.05 studied (Van Raaij et al 1996, Van Ginneken et al 1998. Release of catecholamines from chromaffin tissues stimulated by a decrease in PaO 2 following deep hypoxia was also reported in many fish species.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Cortisol, glucose and lactate concentrations were determined in WB extracts of sticklebacks exposed to two hours or seven days of hypoxia to provide an assessment of the endocrine and metabolic adjustments caused by the treatments (Sneddon and Yerbury 2004;Johansen et al 2006;Van Raaij et al 1996a). Sticklebacks from three separate populations, whose habitats were characterised by differences in the occurrence of hypoxia, were used to test whether hypoxia tolerance varied between populations.…”
Section: Berlinsky 2006)mentioning
confidence: 99%